Factors Influencing Help-seeking Choices Among Non-Service-Connected Survivors of IPV - Ravi, Kristen E. (Journal of family violence, 2024)
BackgroundSubstantial evidence highlights the role of formal intimate partner violence (IPV) services in reducing the negative impacts of IPV for survivors and their families. The decision to seek help and the process survivors navigate in the help-seeking journey is influenced by individual, interpersonal, and sociocultural factors. Understanding why survivors choose not to seek formal services is necessary to better understand their experiences and to improve survivor-centered outreach and support.PurposeThe goal of this study was to understand the perspectives and choices of survivors who are not engaged with IPV services. The primary research question was what factors influence help-seeking choices among non-service-connected IPV survivors.MethodsSemi-structured interviews were conducted with 23 survivors in community settings or over the phone. The researchers used a process of inductive and deductive coding to identify themes and subthemes.ResultsThe researchers identified three themes1) intrapersonal barriers, 2) interpersonal barriers, and 3) macro/systems barriers.ConclusionImplications include identifying factors that facilitate help-seeking to expand services to a wider group of survivors while providing support and information for informal support people, as well as the need for future research to engage and understand the perspectives of survivors who have not sought help from any formal services.